2020
DOI: 10.1080/14942119.2020.1761746
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and cost analysis of tower yarder systems using the Koller 507 and the Valentini 400 in southwest Germany

Abstract: Cable-based timber extraction offers some advantages with regard to impacts to forest stands and soils, and can be used under a wide range of conditions. It is important not only in steep terrain, but also increasingly in flat terrain when soils have low bearing capacity. In this study, utilization data from two commonly used tower yarding systems were analyzed: a tower yarder with a mounted processor (K507) and a medium-distance tower yarder (V400). Collected data included explanatory variables, such as the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Based on a nine-year data collection, the average yarding productivity reported was 10.1 m 3 per productive system hours, including delays up to 15 min (PSH 15 ). Recently, Schweier et al [26] reported an average productivity of 13.3 ± 2.6 m 3 ub /PMH 15 for the same yarder (K507), based on a six-year data collection. Stampfer et al [24] analyzed a comparable yarder (Wanderfalke by Mayr-Melnhof, Austria) and reported average productivities of 12.1-12.5 m 3 per productive system hours, excluding delays (PSH 0 ) (with radio-controlled and standard choker, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a nine-year data collection, the average yarding productivity reported was 10.1 m 3 per productive system hours, including delays up to 15 min (PSH 15 ). Recently, Schweier et al [26] reported an average productivity of 13.3 ± 2.6 m 3 ub /PMH 15 for the same yarder (K507), based on a six-year data collection. Stampfer et al [24] analyzed a comparable yarder (Wanderfalke by Mayr-Melnhof, Austria) and reported average productivities of 12.1-12.5 m 3 per productive system hours, excluding delays (PSH 0 ) (with radio-controlled and standard choker, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Another option is the use of cable crane systems, which completely eliminates ground-based traffic and reduces soil compaction, soil surface damage, and erosion [23]. Studies analyzing yarders that were, however, applied to all directions (but mostly uphill), reported productivities of 10-15 m 3 per productive hour [24][25][26]. Resulting costs were 30-40 €/m 3 for the whole process chain, from manual felling to processing.…”
Section: Introductionmentioning
confidence: 99%
“…We showed that the productivity of each cable-based extraction operation (K301-4 and HAM300) varied by up to 20% between the three harvest units, with the performance differences linked to many reasons. For example, Lindroos and Cavalli [16], Erber et al [23] and Schweier et al [24] reported that the productivity variation in cable yarding operations was due to several reasons such as working conditions and load sizes. In our study, however, during the individual machine tests, the work conditions were similar for the three harvest units (units 1-3 and units [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…The higher productivity efficiency of the K301-4 used in this study demonstrates its higher payload and faster line speed. According to Schweier et al [24] and Engelbrecht et al [28], the operation productivity was affected by the yarder type (heavy or medium) and piece size per cycle. The performance of the heavy yarder ranged from 20% to 30%, depending on the inclusion or exclusion of delay times, since the performance continuously improved with the cycle speed and payload.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the cycle log volume was significantly higher in uphill yarding, particularly in the clear-cut treatment, and the interactions of the yarding direction with the cycle log volume significantly affected the productivity (ANOVA p-value < 0.001). For example, the yarding direction may have affected the productivity for several reasons, such as the carriage movement and stops associated with the haulback line, and operator safety problems when the tower yarders HAM300 [39], K507 [52,53], and URUS MIII [54] were used. Thus, uphill yarding operation activities are more productive than downhill yarding activities.…”
Section: Effect Of Yarding Directions (Uphill Vs Downhill) On Productivitymentioning
confidence: 99%